Modeling entrepreneurial decision-making process using concepts from fuzzy set theory - Islem Khefacha; Lotfi Belkacem (Journal of Global Entrepreneurship Research, 2015)
Entrepreneurship and entrepreneurial culture are receiving an increased amount of attention in both academic research and practice. The different fields of study have focused on the analysis of the characteristics of potential entrepreneurs and the firm-creation process. In this paper, we develop and test an economic-psychological model of factors that influence individuals' intentions to go into business. We introduce a new measure of entrepreneurial intention based on the logic fuzzy techniques. From a practical point of view, this theory offers a natural approach to the resolution of multidimensional and complex problems when the available information is sparse and/or of poor quality. As an illustration, the model is estimated using a data provided by the National Tunisian Global Entrepreneurship Monitor (GEM) 2010 Project, based on the analysis of a sample of 799 cases. A simulation study of the model suggests that entrepreneurial intention is related to a composite of some demographic, competencies, networks and perception factors. This is an important area of concern in entrepreneurship intention which improves our knowledge about the degree to which the individual holds a positive or negative personal valuation about being an entrepreneur. The modeling insights may also be valuable as input to the design of entrepreneurship curricula.
Keywords: 650; Entrepreneurship; Decision-making process; Entrepreneurial intention; Global entrepreneurship monitor (GEM); Fuzzy set theory